The perspectives of sustainable development of Jordanian financial sector in current conditions - S. Yu. Babenkova (Путеводитель предпринимателя)
The Government of Jordan (the Hashemite Kingdom of Jordan) accepted quite an ambitious Economic Action Plan for 2019—2020 where the country's development priorities are clearly defined. The plan is aimed at the development and maintenance of a business-friendly environment, reforms on the financial market and in the social and economic field. However, for mitigating the economic effects caused by the regional crisis and the COVID-19 pandemic, a sufficient financial support is needed, and the Government wants to get it from the International Monetary Fund and World Bank. It is important to note the austerity measures introduced by the Government in May 2018, including an increase in income tax, which resulted in the general strike of major retail store chains and mass riots among the population.Jordan shares borders with two unstable countries: Syria and Iraq. In this regard, all the negative consequences ofwars and conflicts in these countries were an additional burden for the Kingdom's economy.Hence, Jordan must consider the possibility of maintaining its economy not in the projects and Economic Action Plans declared by the Government, but in the geopolitical area. For instance, to restore relationships with Syria and improve relationships with Iraq, develop the activity in the Palestinian territories. Well-considered and balanced political steps are a good approach to solving many local problems, moreover, Jordan has a big potential in the implementation ofvarious innovative approaches.